Case Report: Take a Second Look: Covid-19 Vaccination-Related Cerebral Venous Thrombosis and Thrombotic Thrombocytopenia Syndrome - Braun, Tobias; Viard, Maxime; Juenemann, Martin; Struffert, Tobias; Schwarm, Frank; Huttner, Hagen B.; Roessler, Florian C. (Frontiers in Neurology, 2021)
We present two cases of ChAdOx1 nCov-19 (AstraZeneca)-associated thrombotic thrombocytopenia syndrome (TTS) and cerebral venous sinus thrombosis (CVST). At the time of emergency room presentation because of persistent headache, blood serum levels revealed reduced platelet counts. Yet, one or four days after symptom onset, first MR-angiography provided no evidence of CVST. Follow-up imaging, performed upon headache refractory to non-steroidal pain medication, verified CVST 2-10 days after initial negative MRI. Both patients received combined treatment with intravenous immunoglobulins and parenteral anticoagulation leading to an increase of platelet concentration in both individuals, and resolution of the occluded cerebral sinus in one patient.